Pelatihan Sistem Akuntansi Berbasis Excel dengan penerapan ISAK 35 dan PSAK 109 sebagai Upaya Peningkatan Akuntabilitas Sosial (Pada Pengurus Masjid di Desa Balong Wangi) - Ma’rufatur Rodhiyah; Ardianah Asyhsanul Hayat; Amanatul Khoriyah; Dwi Pertiwi; Laily Nikmah (Pusat Riset dan Inovasi Nasional, 2022)
This PKM activity aims to provide assistance and training for mosque administrators in Balong Wangi village and provide knowledge about how to prepare mosque financial reports using an Excel-based application. In this way, financial reports can be accounted for accurately and accountably. The method for implementing this service program is data collection and observation, implementation of activities, and evaluation. The results of this activity received a positive response from the activity participants/partners. Mosque administrators believe that training and assistance in preparing financial reports according to financial accounting standards based on the Excel program can increase their knowledge and make it easier for them to prepare financial reports. This training can improve administrator skills and the accuracy of financial reporting. The impact of this activity is that mosque administrators can more easily and efficiently prepare financial reports.